Nano mechanical study on a single layer TiC/TI6Al4V-ELI composite manufactured with laser metal deposition - Ramasobane Pushetso; Mashinini Madindwa Peter; Masina Bathusile Nelisiwe (MATEC Web of Conferences, 2023)
This study investigated the nano mechanical properties of Ti6Al4V-ELI embraced with TiC particles, synthesized with in situ laser metal deposition technique. The 3.85% feed ratio fraction TiC/Ti6Al4V-ELI composite samples were manufactured at four varying energy densities. The beta grain boundary and the acicular alpha primary matrix were found to have diverse morphologies of carbide particles due to the in-situ reaction. The effect of energy density is observed on the microstructure and nano mechanical properties. An average off set of 650 nm was recorded after the nano-indentation in the matrix at a maximum load of 400 mN.